2021
DOI: 10.1016/j.celrep.2021.109699
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Tim-3 drives phenotypic and functional changes in Treg cells in secondary lymphoid organs and the tumor microenvironment

Abstract: SUMMARY Regulatory T cells (Treg cells) are critical mediators of self-tolerance, but they can also limit effective anti-tumor immunity. Although under homeostasis a small fraction of Treg cells in lymphoid organs express the putative checkpoint molecule Tim-3, this protein is expressed by a much larger proportion of tumor-infiltrating Treg cells. Using a mouse model that drives cell-type-specific inducible Tim-3 expression, we show that expression of Tim-3 by Treg cells is sufficient to drive Treg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 65 publications
2
33
1
1
Order By: Relevance
“…This may explain our results, in which activation of CD8 + T cells, as well as the high abundance of memory T cells, significantly prolongs the OS time of CC patients. Surprisingly, the results showed that high Treg infiltration was significantly associated with good prognosis of patients, which was quite opposite to the phenomenon widely reported thus far ( Banerjee et al, 2021 ; Dahlhoff et al, 2021 ; Peng et al, 2021 ). In previous reports, little literature has mentioned that Treg can participate in the immune process as a protective factor.…”
Section: Discussioncontrasting
confidence: 98%
“…This may explain our results, in which activation of CD8 + T cells, as well as the high abundance of memory T cells, significantly prolongs the OS time of CC patients. Surprisingly, the results showed that high Treg infiltration was significantly associated with good prognosis of patients, which was quite opposite to the phenomenon widely reported thus far ( Banerjee et al, 2021 ; Dahlhoff et al, 2021 ; Peng et al, 2021 ). In previous reports, little literature has mentioned that Treg can participate in the immune process as a protective factor.…”
Section: Discussioncontrasting
confidence: 98%
“…TIM-3 is expressed on fully differentiated Th1 cells and activated by binding to its ligand galectin-9 [137]. This leads to termination of Th1-driven immunity and an increased Tregs suppressive activity [137][138][139]. In cervical cancer, various immune checkpoints were often co-expressed on effector T cells and elevated upon metastatic involvement in TDLN [140], observations consistent with the acquisition of an exhausted phenotype.…”
Section: T-cell Activation and Inhibitionmentioning
confidence: 74%
“…TIM-3+ Treg cells have been associated with multiple cancers including CRC and have a role in regulating immune responses by driving T cell inhibition or exhaustion. They express CD39/CD73 (Figure 1F), IL-10, and TGF-b (Figure 1D) and upregulate the expression of checkpoint receptors (Figure 1G), such as CTLA-4, PD-1, and LAG-3 (166)(167)(168)(169)(170). CRC tumors implanted in TIM-3 deficient mice have a reduced infiltration of Treg cells, reduced CD8+ Teff cell exhaustion, and slower tumor growth (170).…”
Section: Tumor-infiltrating Treg Cells and Crcmentioning
confidence: 99%